The physiological and morphological characteristics of a Kenyan world-class long-distance runner: A case study - Yoshioka, T.; Nakagaki, K.; Nakamura, K.; Mukai, N.; Nabekura, Y. (International Journal of Sport & Health Science, 2023)
The purpose of this study was to compare the physiological and morphological characteristics of J. Ndambiri, a Kenyan world-class long-distance runner (10,000 m personal best: 27:04.79), with runners belonging to the national corporate team (29:32.18±0:30.35). Oxygen uptake (VO2), heart rate, blood lactate concentration and stride frequency were measured during submaximal exercise on a treadmill (270, 290, 310, 330, 350 and 370 m/min velocities with 1% inclination). Peak oxygen uptake (VO2peak) was determined during the maximal exercise test. In addition, morphological parameters (length of thigh and shank, maximum circumference of thigh and shank, and cross-sectional area of the trunk, thigh and shank muscles) were determined using a tape measure and magnetic resonance imaging (MRI). Ndambiri was superior to Japanese runners in terms of not only running economy (65.0 vs 69.8 ±1.9 ml/kg/min at 330 m/min), but also blood lactate concentration (1.50 vs 2.59±0.74 mmol/l at 330 m/min), heart rate (159.8 vs 170.8±4.0 bpm at 330 m/min) during the submaximal running test and VO2peak (80.8 vs 76.3±2.4 ml/kg/min). In addition, the morphological characteristics of Ndambiri were also quite different from those of Japanese runners. In particular, Ndambiri's maximum shank circumference was much smaller than that of Japanese runners (32.0 vs 35.8±1.8 cm). Furthermore, the cross-sectional area of the gastrocnemius muscle, which composes the shank, was significantly correlated with the oxygen cost of running at 330 m/min (r=0.700). These findings indicate that the superior performance of Ndambiri is attributable to various factors such as a higher VO2peak, lower blood lactate concentration and heart rate, as well as running economy. In the future, it will be necessary to clarify the factors supporting these relationships between physiological variables and morphological characteristics.